Use of a novel triple-tracer approach to assess postprandial glucose metabolism - BASU, Rita; DI CAMILLO, Barbara; TOFFOLO, Gianna; BASU, Ananda; SHAH, Pankaj; VELLA, Adrian; RIZZA, Robert; COBELLI, Claudio (American journal of physiology: endocrinology and metabolism, 2003)
Numerous studies have used the dual-tracer method to assess postprandial glucose metabolism. The present experiments were undertaken to determine whether the marked tracer nonsteady state that occurs with the dual-tracer approach after food ingestion introduces error when it is used to simultaneously measure both meal glucose appearance (Ra meal) and endogenous glucose production (EGP). To do so, a novel triple-tracer approach was designed: 12 subjects ingested a mixed meal containing [1-13C]glucose while [6-3H]glucose and [6,6-2H2]glucose were infused intravenously in patterns that minimized the change in the plasma ratios of [6-3H]glucose to [1-13C]glucose and of [6,6-2H2]glucose to endogenous glucose, respectively. Ra meal and EGP measured with this approach were essentially model independent, since non-steady-state error was minimized by the protocol. Initial splanchnic glucose extraction (ISE) was 12.9% plus or minus 3.4%, and suppression of EGP (EGPS) was 40.3% plus or minus 4.1%. In contrast, when calculated with the dual-tracer one-compartment model, ISE was higher (P < 0.05) and EGPS was lower (P < 0.005) than observed with the triple-tracer approach. These errors could only be prevented by using time-varying volumes different for Ra meal and EGP. Analysis of the dual-tracer data with a two-compartment model reduced but did not totally avoid the problems associated with marked postprandial changes in the tracer-to-tracee ratios. We conclude that results from previous studies that have used the dual-tracer one-compartment model to measure postprandial carbohydrate metabolism need to be reevaluated and that the triple-tracer technique may provide a useful approach for doing so.